1993
DOI: 10.1007/bf01066417
|View full text |Cite
|
Sign up to set email alerts
|

Contextual probability evaluation in autistic, receptive developmental language disorder, and control children: Event-related brain potential evidence

Abstract: Compared 8- to 14-year-old children with either autism or receptive developmental language disorder (RDLD) to age- and IQ-matched normal controls in their ability to detect both frequent (p = .70) and infrequent (p = .30) randomly presented auditory stimuli under task and no-task conditions. Event-related brain potentials (ERPs), behavioral reaction times, and target detection accuracy rates were measured. Although the three groups of children performed in a similar manner on behavioral measures, only the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 12 publications
6
43
0
2
Order By: Relevance
“…Further, neither the acoustic complexity nor the ''speechness'' quality of these stimuli affected the sensory discrimination of pitch in the autism group, as shown by their normal MMN amplitudes. This finding is in good agreement with the generally good behavioral performance on auditory target (acoustically simple and complex) detection tasks by adults and adolescents with autism (6,7,11) and with the normal behavioral pitch discrimination abilities in adults with autism (18).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Further, neither the acoustic complexity nor the ''speechness'' quality of these stimuli affected the sensory discrimination of pitch in the autism group, as shown by their normal MMN amplitudes. This finding is in good agreement with the generally good behavioral performance on auditory target (acoustically simple and complex) detection tasks by adults and adolescents with autism (6,7,11) and with the normal behavioral pitch discrimination abilities in adults with autism (18).…”
Section: Discussionsupporting
confidence: 78%
“…They include abnormalities in spontaneous looking (3), focused attention (5)(6)(7)(8)(9)(10)(11), and voluntary shifting of attention (12)(13)(14). Courchesne et al (12) proposed that the majority of the attentional deficits observed in autism might be caused by a cerebellar dysfunction that slows down the adaptation of the neural systems to the constantly changing neural processing demands.…”
mentioning
confidence: 99%
“…In a follow up study using a missing-stimulus paradigm (described previously), high functioning adolescents with autism showed a smaller P3b, despite normal performance on the task, when compared to age matched controls (Courchesne et al 1984(Courchesne et al , 1985aCourchesne et al 1989). Two further studies by the same group showed a similar pattern of smaller P3b despite normal performance (Ciesielski et al 1990;Lincoln et al 1993). Taken together, these findings suggest that while there are likely differences in novelty processing, because performance is normal, individuals with autism may be using "unusual or alternate physiological processes to detect target events" .…”
Section: Higher-level (Cognitive) Processing: P3b and Ncmentioning
confidence: 81%
“…Most studies carried out in autism on electrical responses associated with novelty processing have involved active novel-target detection. Results showed that the response is significantly smaller in children with autism compared to controls (Courchesne et al, 1984(Courchesne et al, , 1985Lincoln et al, 1993;Kemner et al 1995). P3a in response to novel speech stimuli in a no-task condition has been shown to be reduced in autism (Čeponienè et al, 2003).…”
Section: Introductionmentioning
confidence: 99%